Experimental investigation on ultrasonic shot peening of WC-Co alloy. Issue 14 (25th October 2020) - Zhu, Shengjian; Hu, Yifeng; Zhang, Xuehui; Zou, Yangjun; Ahmad, Tahir; Zhang, Wenglong; Tang, Fuqian; Liang, Tongxiang
ABSTRACT: Ultrasonic surface shot peening (USSP) treatment was conducted on the WC-8Co composite. The effects of different USSP-treated time on surface roughness, microstructure, mechanical and corrosion resistance were investigated. The results show that continuous bombardment on the surface of WC-8Co cemented carbide induced by high kinetic energy particles during USSP makes the WC particles and Co phase broken and refined. A nanostructured layer is generated on the top-surface of WC-Co cemented carbide and the thickness is about 3.14 µm. Due to the polishing and washing of all samples, the results of surface roughness don't change much. Microhardness of nanostructured surface layer increases by 15.8% compared with the untreated sample. Electrochemical experiment results indicated that the refinement of grain are the main reasons for the enhanced corrosion behavior of the samples. At the same time, the most suitable shot peening time of USSP for WC-8Co cemented carbide is 30 min.